Modeling as a STEM technology for developing creativity in primary education students - Mukhina, Tetiana (Kharkiv : H. S. Skovoroda Kharkiv National Pedagogical University, 2025)
The article reveals the role of modeling as an effective means of developing creative thinking of future primary school teachers within the STEM approach. The theoretical foundation of the research is based on the constructivist approach, which emphasizes the active role of the student in creating and exploring models to develop cognitive structures and critical thinking. It is determined that STEM modeling contributes to the formation of skills to formulate hypotheses, visualize ideas, and seek non-standard solutions using LEGO, digital simulators, and 3D technologies. A methodological system of professional training for educators is outlined, including the use of the case method, project-based activities, and digital platforms (Tinkercad, Scratch, GeoGebra) for modeling educational content and methods. Practical significance is supported by examples of projects such as "Ecological House" and "Solar System Model," which promote the development of technical literacy and teamwork.
Keywords: STEM education; modeling; creative thinking; future primary school teachers; professional training; constructivism; digital platforms; project-based activities